2007
DOI: 10.1016/j.devcel.2006.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Hair Development and Apparent Follicular Transformation to Mammary Gland in the Absence of Hedgehog Signaling

Abstract: SummaryWe show that removing the Shh signal tranducer Smoothened from skin epithelium secondarily results in excess Shh levels in the mesenchyme. Moreover, the phenotypes we observe reflect decreased epithelial Shh signaling, yet increased mesenchymal Shh signaling. For example, the latter contributes to exuberant hair follicle (HF) induction, while the former depletes the resulting follicular stem cell niches. This disruption of the niche apparently also allows the remaining stem cells to initiate hair format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 34 publications
(25 reference statements)
5
63
0
Order By: Relevance
“…However, the level and/or timing of Shh expression might be an important effector. Suggestively, inhibition of Shh signaling resulted in glandular tissue formation in back skin, which otherwise harbors only hair follicles (Gritli-Linde et al, 2007). In addition, consistent with this notion, we found that Shh expression was very low in early sweat gland induction stages and then increased sharply during postnatal secretory coil formation .…”
Section: Shh Action: An Example Of Variable Involvement and Timing Insupporting
confidence: 76%
“…However, the level and/or timing of Shh expression might be an important effector. Suggestively, inhibition of Shh signaling resulted in glandular tissue formation in back skin, which otherwise harbors only hair follicles (Gritli-Linde et al, 2007). In addition, consistent with this notion, we found that Shh expression was very low in early sweat gland induction stages and then increased sharply during postnatal secretory coil formation .…”
Section: Shh Action: An Example Of Variable Involvement and Timing Insupporting
confidence: 76%
“…40,50 The appearance of Gli2 in hepatocytic cells was surprising because during development and repair of other tissues, Hh ligand production is most conspicuous in epithelial cells and Hh target gene expression localizes in mesenchymal cells. 20,51,52 Following even mild acute or chronic injury to hepatocytes, however, we noted that expression of the Hh ligand, Ihh, and the Hh target, Gli2, tended to localize in very close proximity (and possibly colocalize) within bile ductular cells in ethionine-treated mice with NASH. Cells that coexpress epithelial and mesenchymal genes are generally considered to be undergoing epithelial-tomesenchymal (or mesenchymal-to-epithelial) transition.…”
Section: Hedgehog Activity and Nash Sv Fleig Et Almentioning
confidence: 84%
“…It is likely that MFG secretion is a highly derived form of apocrine secretion in which upregulation of milk fat secretion has required incorporation of novel membrane constituents (see Milk Fat Globule section, below). Unfortunately, little is known about the details of secretion in generalized apocrine glands or about the genes expressed and proteins synthesized (Oftedal, 2002b), although at least some types do not produce milkspecific proteins, such as b-casein (Gritli-Linde et al, 2007). From an evolutionary perspective, it would be very interesting to compare the array of genes expressed by developing and secreting apocrine glands with those expressed during mammary gland development, milk secretion, and mammary involution.…”
Section: The Evolution Of Mammary Secretionmentioning
confidence: 99%